Comparative Analysis of Corrosion Inhibition: Between Jatrophacurcas, Palm and Diesel Oil based Emulsified Acids for Acid Stimulation Operations - Yousufi, M.M. (Institute of Physics Publishing, 2018)
The recent environmental concerns have raised the need for a green acidizing fluid, which is able to replace diesel oil as an oil phase in emulsion based acidizing fluids. In order to do so it must be able to provide not only retardation in acid reaction against the rock surface, but also provide suitable inhibition characteristic that can reduce the amount of corrosion which occurs due to acidizing. In this paper emulsified acids made from triglyceride oils namely; Jatropha curcas oil and Palm oil have been tested for corrosion inhibition in comparison with Diesel oil based emulsified acid and 15wt. HCl. The emulsion made with Jatropha curcas oil showed capability to replace diesel oil as a viable and an environmental friendly substitute for oil phase in emulsified acids. Â© Published under licence by IOP Publishing Ltd.